The novel family of Warbicin® compounds inhibits glucose uptake both in yeast and human cells and restrains cancer cell proliferation - Vanthienen, Ward; Fernández-García, Juan; Baietti, Maria Francesca; Claeys, Elisa; Van Leemputte, Frederik; Nguyen, Long; Goossens, Vera; Deparis, Quinten; Broekaert, Dorien; Vlayen, Sophie; Audenaert, Dominique; Delforge, Michel; et al. (Frontiers in Oncology, 2024)
Many cancer cells share with yeast a preference for fermentation over respiration, which is associated with overactive glucose uptake and breakdown, a phenomenon called the Warburg effect in cancer cells. The yeast tps1∆ mutant shows even more pronounced hyperactive glucose uptake and phosphorylation causing glycolysis to stall at GAPDH, initiation of apoptosis through overactivation of Ras and absence of growth on glucose. The goal of the present work was to use the yeast tps1∆ strain to screen for novel compounds that would preferentially inhibit overactive glucose influx into glycolysis, while maintaining basal glucose catabolism. This is based on the assumption that the overactive glucose catabolism of the tps1∆ strain might have a similar molecular cause as the Warburg effect in cancer cells. We have isolated Warbicin ® A as a compound restoring growth on glucose of the yeast tps1∆ mutant, showed that it inhibits the proliferation of cancer cells and isolated structural analogs by screening directly for cancer cell inhibition. The Warbicin ® compounds are the first drugs that inhibit glucose uptake by both yeast Hxt and mammalian GLUT carriers. Specific concentrations did not evoke any major toxicity in mice but increase the amount of adipose tissue likely due to reduced systemic glucose uptake. Surprisingly, Warbicin ® A inhibition of yeast sugar uptake depends on sugar phosphorylation, suggesting transport-associated phosphorylation as a target. In vivo and in vitro evidence confirms physical interaction between yeast Hxt7 and hexokinase. We suggest that reversible transport-associated phosphorylation by hexokinase controls the rate of glucose uptake through hydrolysis of the inhibitory ATP molecule in the cytosolic domain of glucose carriers and that in yeast tps1∆ cells and cancer cells reversibility is compromised, causing constitutively hyperactive glucose uptake and phosphorylation. Based on their chemical structure and properties, we suggest that Warbicin ® compounds replace the inhibitory ATP molecule in the cytosolic domain of the glucose carriers, preventing hexokinase to cause hyperactive glucose uptake and catabolism.